C-reactive protein as a possible modifier of Lipoprotein(a)-related risk for coronary heart disease in Europe: results from the BiomarCARE project. (3rd October 2022) - Arnold, N; Blaum, C; Gossling, A; Zeller, T; Linneberg, A; Soderberg, S; Iacoviello, L; Sans, S; Leoni, V; Kee, F; Salomaa, V; Kuulasmaa, K; et al.
Abstract: Background: Lipoprotein(a) (Lp(a)) represents a unique proatherogenic lipoprotein with potent pro-thrombotic and pro-inflammatory properties. Recent studies demonstrated that Lp(a)-associated risk for cardiovascular disease (CVD) was significantly increased only in individuals with a high inflammatory burden (i.e. hsCRP levels >2 mg/L). However, these results have been either based on a post-hoc analysis in a highly selected study population with a high/very high CVD risk, or conducted within a multi-ethnic population with significant variation in Lp(a) levels. Purpose: The main aim was to investigate whether hsCRP concentration modulates the predictive value of Lp(a) for coronary heart disease (CHD) events in the general population across Europe. Methods: Data of 87, 760 participants from 10 European prospective population-based cohorts, participating in the Biomarkers for Cardiovascular Risk Assessment in Europe (BiomarCaRE)-project, were used for the present analysis (79, 958 subjects without and 7, 189 individuals with established CHD at baseline (primary/secondary prevention cohorts, respectively)). All Lp(a) measurements were performed in the central BiomarCaRE laboratory. Fine and Gray competing risk-adjusted models stratified by study cohort were calculated to assess the association between Lp(a) levels and future CHD events stratified according to hsCRP levels (<1 mg/l, ≥1–<2 mg/l and ≥2 mg/l). Results: During a median follow-up of 11.3 years, 4, 928 events occurred in the CHD-free subpopulation and 1, 772 events occurred in the CHD subpopulation. In the primary prevention cohort, increased Lp(a) was significantly associated with future CHD events irrespective of hsCRP: Hazard ratios (HRs) for future CHD events (top vs bottom quintile (Q) of Lp(a) distribution) were 1.46 (95% CI: 1.21–1.78; p<0.001) in those having a hsCRP concentration <1 mg/l; 1.32 (95% CI: 1.09–1.61; p=0.0052) for a hsCRP group of ≥1-<2 mg/l and 1.40 (95% CI: 1.22–1.61; p<0.001) in subjects with a hsCRP concentration ≥2 mg/l, after multivariable adjustment for traditional CV risk factors including LDL-Ccorr and lipid-lowering medication. In contrast, in the secondary prevention, we found no association between increased Lp(a) levels and CHD events in individuals with a very low inflammatory burden (HR for hsCRP <1 mg/l 0.92 (95% CI 0.63–1.34), p=0.66, Q5 vs Q1)), whereas the association was significant among subjects with a hsCRP concentration ≥1 mg/l (HRs: 1.43 (95% CI: 1.01–2.03; p=0.045) for hsCRP group ≥1-<2 mg/l and 1.35 (95% CI: 1.07–1.71; p=0.013) for hsCRP group ≥2 mg/l (both for Q5 vs Q1)). Conclusion: In a primary prevention setting, Lp(a) was associated with incident CHD irrespective of the inflammatory burden. In contrast, among subjects with known CHD, the association of Lp(a) and future CHD events was only present in those with hsCRP levels >1 mg/l. These findings might guide target population selection for upcoming Lp(a)-targeting compounds. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): This work was supported by the 7th Framework Programme Collaborative Project (grant agreement no. HEALTH-F2-2011-278913). The MORGAM Project has received funding from EU projects MORGAM (Biomed, BMH4-CT98-3183), GenomEUtwin (Fifth Framework Programme FP5, QLG2-CT-2002-01254), ENGAGE (FP7, HEALTH-F4-2007-201413), CHANCES (FP7, HEALTH-F3-2010-242244), BiomarCaRE (FP7, HEALTH-F2-2011-278913), euCanSHare (Horizon 2020, No. 825903) and AFFECT-EU (Horizon 2020, No. 847770); and Medical Research Council, London (G0601463, No. 80983: Biomarkers in the MORGAM Populations).